2020
DOI: 10.1016/j.jneumeth.2020.108685
|View full text |Cite
|
Sign up to set email alerts
|

Advances in modelling alpha-synuclein-induced Parkinson’s diseases in rodents: Virus-based models versus inoculation of exogenous preformed toxic species

Abstract: Aggregates of alpha-synuclein (αSyn) have been described in Parkinson's disease (PD) patients, and recent evidence has suggested that the most toxic αSyn species in PD are small soluble aggregates including oligomers, prefibrils, protofibrils. The physiological function of αSyn is still highly debated, with a possible role in synaptic vesicle trafficking and release at the presynaptic compartment, and in the regulation of gene expression in the nucleus. Emerging evidence indicate that most of αSyn functions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 220 publications
(336 reference statements)
2
14
0
Order By: Relevance
“…The data presented here showing that proSAAS exerts strong protection from aSyn-induced nigro-striatal DA tract degeneration provide the first in vivo evidence of the potential utility of this chaperone as a therapeutic target for PD. AAV-mediated overexpression of human wildtype aSyn unilaterally in the rat SNc produced a robust progressive motor asymmetry over an 8-week period accompanied by significant loss of TH-positive nigral cells and TH-positive striatal terminals measured post-mortem, consistent with previous reports describing similar viral-mediated aSyn models (reviewed in (36)). All three of these measures of aSyn toxicity were profoundly blunted by nigral co-injection of proSAAS-expressing lentivirus.…”
Section: Discussionsupporting
confidence: 89%
“…The data presented here showing that proSAAS exerts strong protection from aSyn-induced nigro-striatal DA tract degeneration provide the first in vivo evidence of the potential utility of this chaperone as a therapeutic target for PD. AAV-mediated overexpression of human wildtype aSyn unilaterally in the rat SNc produced a robust progressive motor asymmetry over an 8-week period accompanied by significant loss of TH-positive nigral cells and TH-positive striatal terminals measured post-mortem, consistent with previous reports describing similar viral-mediated aSyn models (reviewed in (36)). All three of these measures of aSyn toxicity were profoundly blunted by nigral co-injection of proSAAS-expressing lentivirus.…”
Section: Discussionsupporting
confidence: 89%
“…Apart from the pre-synaptic terminal, potent membrane binding capabilities of a-syn have also been identified in organelles such as mitochondria [38,52,93,94], the endoplasmic reticulum [95,96], the Golgi apparatus [97][98][99] and the nucleus [100]. Multiple forms of a-syn disrupt protein synthesis and degradation pathways, restrict intracellular calcium handling, increase oxidative stress, and impair phagocytic activity [52,101].…”
Section: Changes In Organelle Functionmentioning
confidence: 99%
“…The use of oligomers or PFFs, either injected into the brain [71,140,141], or into the gut [76,142] is a second tool that has recently gained traction and is increasing our understanding of the nature of a-syn spread within the brain. PFFs cause robust DA cell death and show extensive spread of a-syn pathology across brain regions [100,143,144]. Ser-129 phosphorylation of endogenous a-syn in response to extracellular a-syn fibrils exerts profound effects on the ability of a-syn to form toxic aggregates [143], and may be of particular relevance to the spread of a-syn pathology across brain regions.…”
Section: Additional Tools To Model A-syn Pathology Pd In Rodentsmentioning
confidence: 99%
“…For neuropsychiatric disorders, such as schizophrenia, common symptoms such as paranoid delusions and auditory hallucinations are uniquely human and make interpretation of results acquired from animal models particularly challenging (Canetta and Kellendonk, 2018). Although imperfect, there are multiple available models of schizophrenia (Winship et al, 2019), depression (Planchez et al, 2019), and other neuropsychiatric (Nestler and Hyman, 2010) as well as neurodegenerative disorders (Dawson et al, 2018;Carta et al, 2020) that, to varying degrees, possess face validity (observed characteristics/symptoms that have clinical correlates in the human patient population), construct validity (key neurobiological/pathological bases of the human disorder), and/or predictive validity (expected pharmacological response to efficacious drugs currently used to treat the human disorder). Each animal model has its advantages and caveats (Fisher and Bannerman, 2019), and evaluation of hypotheses as well as potential drugs across models undoubtedly provides better predictive value for translation to human studies, particularly when repurposed drugs (such as IMiDs) are evaluated at a clinically translatable dose (Becker and Greig, 2010;Seeman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%